RFID sourcebook - Lahiri, Sandip (IBM Press, 2006)
"Approaching crucial decisions about Radio Frequency Identification (RFID) technology? This book will help you make choices that maximize the business value of RFID technology and minimize its risks. IBM's Sandip Lahiri, an experienced RFID solution architect, presents up-to-the-minute insight for evaluating RFID; defining optimal strategies, blueprints, and timetables; and deploying systems that deliver what they promise." "Drawing on his experience, Lahiri offers candid assessments of RFID's potential advantages, its technical capabilities and limitations, and its business process implications. He identifies pitfalls that have tripped up early adopters, and shows how to overcome or work around them. This must-have resource can also act as a reference guide to any nontechnical person who wants to know about the technology."--Jacket.